2017
DOI: 10.1109/tbme.2016.2606538
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Continuous, Noninvasive, Cuff-Less Measurement of Blood Pressure: Evaluation in Patients With Nonalcoholic Fatty Liver Disease

Abstract: Abstract-Objective: One promising approach for a continuous, non-invasive, cuff-less ambulatory BP monitor is to measure the pulse wave velocity or the inversely proportional pulse transit time (PTT), based on electrical and optical physiological measurements in the chest area. A device termed IsenseU-BP+ has been developed for measuring continuous BP, as well as other physiological data. The objective of this paper is to present results from the first clinical evaluation with a wide range of patients. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…M1 is the modality with the most data points and the strongest r. M1 is also the only category to include studies with sample sizes over 30, making the correlations stronger than those of studies with small sample sizes. Across most modalities, SBP estimations have consistently higher correlations with real SBP than DBP estimations do with real DBP [17,21,23,25,27,40,43,44,51,52,55,60,61,65,81,82]. Three studies from M2 [15], M1 [59], and M1 [67] showed the opposite trend and two studies from M1 [31] and M4 [20] reported the same r for both SBP and DBP.…”
Section: Global Distribution and Combinations Of Biosignals Used In Lmentioning
confidence: 90%
See 2 more Smart Citations
“…M1 is the modality with the most data points and the strongest r. M1 is also the only category to include studies with sample sizes over 30, making the correlations stronger than those of studies with small sample sizes. Across most modalities, SBP estimations have consistently higher correlations with real SBP than DBP estimations do with real DBP [17,21,23,25,27,40,43,44,51,52,55,60,61,65,81,82]. Three studies from M2 [15], M1 [59], and M1 [67] showed the opposite trend and two studies from M1 [31] and M4 [20] reported the same r for both SBP and DBP.…”
Section: Global Distribution and Combinations Of Biosignals Used In Lmentioning
confidence: 90%
“…The use of devices with SCG, BCG, and ICG has not been widely validated or accepted, largely owing to their susceptibility to error caused by motion artifacts and device complexity with an extra sensor [33,61]. Interestingly, one of the highest correlations (0.92 and 0.85 for SBP and DBP, respectively) was reported by a study [23] that investigated a combination of PPG, ECG, and SCG during static exercise; however, this method has not yet been validated during ambulation or for individuals other than young healthy males.…”
Section: Accuracy Of Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 1, the usual wearable and portable devices are the finger probe, 39,40 wristband, 40–42 armband, 17,43 chest belt 44 , and vest. 45 Bluetooth and ZigBee are the most utilized transmission mode.…”
Section: Application Of Ppg In Mobile and Wearable Health Devicesmentioning
confidence: 99%
“…The impacting factors were various, for example, age, gender, height, weight, and cardiovascular disease. Seeberg et al [32], Li et al [33], and Martin et al [3] reported similar results for healthy subjects when they did subject-by-subject correlations. Some subjects in the present study had extremely strong correlations between SBP and PAT, but other subjects showed weak correlations.…”
Section: Discussionmentioning
confidence: 70%